The me that remains [compact disc] - Grant, Amy (Amy Grant Productions, 2026)
Amy Grant's new album explores how to face today's unrest without rushing to fix it. Drawing on imagery from Woodstock and cultural history, the song reflects on shared confusion and the need to see through others' perspectives. It urges presence, collective problem-solving, and hope that by choosing empathy, we can shape a better path forward together.